Model-free global sliding mode control using adaptive fuzzy system under constrained input amplitude and rate for mechatronic systems subject to mismatched disturbances - He, Dingxin; Wang, Haoping; Tian, Yang; Precup, Radu-Emil (Information sciences, 2025)
An n-DOF mechatronic systems with uncertain dynamics, mismatched disturbances, and input amplitude and rate saturations can hardly be modeled well such that model-based control approaches become infeasible. In this paper, a model-independent solution only using input-output data of mechatronic system is innovatively provided. Together with a fractional-order time-delay estimation and a fuzzy logic system, a fractional-order ultra-local model-based fuzzy global sliding mode saturated controller (FO-FGSMSC) is naturally developed to pursue superior performance and constrained control input simultaneously. Prominent advantages are presented as follows: 1) The proposed fractional-order ultra-local model can not only reduce the complexity of controller design, but also enhance the flexibility and adaptability. 2) The global sliding mode control scheme stabilizes the closed-loop system and guarantees the global robustness. 3) The amplitude and rate of the generated control torque are both constrained, which is more favorable to practical implementations. Afterward, the stability analysis of the closed-loop system with FO-FGSMSC is presented by the Lyapunov theory. Finally, the numerical simulation on 2-DOF robotic manipulator, co-simulations on PUMA 560 3-DOF robotic manipulator and iReHave 7-DOF upper limb exoskeleton, and experiment on 2-DOF upper limb exoskeleton are completed. The obtained results demonstrate the effectiveness and superiority of the designed control approach.